Strategies Used to Translate the Dialogue Texts and Narrations in Raider of the Copper Hill - Agnes Bonita Setiawan; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2024)
Translators employ strategies as not every word has its direct equivalence in another language. This study aims to examine the strategies employed in the translation of dialogue texts and narrations found in Raider of the Copper Hill into Indonesian. Furthermore, the writer employs a qualitative approach using Baker’s (2018) strategies to examine each dialogue text and narration in the comic and see whether the strategies succeed in maintaining the meaning. Baker’s (2018) strategies the translator uses to translate the dialogue texts, namely: translation by a more general word, by a less expressive word, by cultural substitution, using a related word, by paraphrase using unrelated words, and by omission. To translate the narrations, the translator employs the same strategies except the less expressive word strategy. However, some tones and humor contained in the texts get altered.